The The Role of Reading Corners in Improving the Reading Ability of the 3rd Graders at SDN 12 Singkawang - Riko Ngepkep Ginting; Mertika; Lili Yanti (LPPM Universitas PGRI Semarang, 2025)
In this era of globalization, reading skills are really necessary. Because the reality shows that science, technology and arts (IPTEKS) continue to develop. This research aims to determine: 1) determine the reading ability of elementary school students; 2) know the reading corner facilities at school; 3) determine the role of reading corners in improving elementary school students' reading skills. The type of research used is descriptive qualitative research. This research was conducted at SDN 12 Singkawang. The subject of this research is the main informant, a class III student at SDN 12 Singkawang with a supporting informant, namely a class III teacher at SDN 12 Singkawang. The data collection techniques and instruments used were observation, interviews and documentation. The results of the research show that (1) the reading ability of students in class III is quite good, many students are already fluent in reading, only a few are still reading poorly or still spelling; (2) the reading corner facilities in classes III A and III B are adequate, namely, in one of the classes there are facilities such as a water dispenser, a fairly comfortable reading area and a reading corner that attracts students' attention to always read books; (3) the role of the reading corner in class III is very useful for students in that class because it can increase students' interest in reading and can improve students' reading abilities. The reading corners at SDN 12 Singkawang are located in every corner of the classroom and are decorated with various kinds of decorations that can make students interested in reading books in the reading corners.